The study on Muslim awareness towards funeral prearrangement industry in Malacca / Nurul Atiqah Saiful Azman - Saiful Azman, Nurul Atiqah (Faculty of Business and Management, 2016)
Purpose – People tend to emphasize on planning the living cost and forgot on how to prepare for their death. Prepaid or prearranged funeral service started to spread across the region in Malaysia, yet still limited in number, especially for Muslims. In the city area, especially, we still lack of such institution who offers Islamic funeral service. the aim of this study is to examine the awareness of Muslim community about the funeral prearrangement industry in Malacca City. By assessing the consciousness level of Muslims about the industry, we can understand better about the opportunity and the direction of this service in future and find ways to help public to make a better decision regarding their pre-need. Methodology – 150 respondents were selected among public randomly using convenience-sampling technique. This study used questionnaires as a tool and it focused on the relationship of knowledge, promotion and previous experience towards awareness level of Muslim on funeral prearrangement concept. Findings Summary – All three variables tested have positive relationship towards awareness level. The results also showed that knowledge is the most influential factor towards the Muslim community awareness about the funeral prearrangement industry in Malacca City.